Evaluation of retinal nerve fiber and ganglion cell layer abnormalities using optical coherence tomography in thyroid-associated orbitopathy - Andrade, Alisson Lima [UNESP]; Faria, Thiago Pereira [UNESP]; Meneghim, Roberta Lilian Fernandes de Sousa; Hashimoto, Mitsuo [UNESP]; Jorge, Edson Nacib [UNESP]; Schellini, Silvana Artioli [UNESP]; Jorge, Eliane Chaves [UNESP] (GN1 Sistemas e Publicacoes, 2025)
PURPOSE: This study aimed to evaluate abnormalities in the retinal nerve fiber layer and ganglion cell layer in patients with thyroid-associated orbitopathy using optical coherence tomography and to examine their relationship with disease severity. METHODS: A cross-sectional study was conducted involving 74 participants, comprising 45 individuals with thyroid-associated orbitopathy and 29 healthy controls. All subjects underwent a comprehensive ophthalmological examination and optical coherence tomography using the Cirrus HD-OCT. The clinical activity score and the European Group on Graves' Orbitopathy severity were also evaluated. RESULTS: In the thyroid-associated orbitopathy group, the mean peripapillary retinal nerve fiber layer thickness was significantly reduced in the temporal quadrant (p<0.05). No significant differences were found in ganglion cell layer thickness across all sectors when compared with the control group. Besides, a significant correlation was observed between orbitopathy severity and decreased mean peripapillary retinal nerve fiber layer thickness (p<0.001). CONCLUSION: Optical coherence tomography may serve as a useful tool for identifying changes in the retinal nerve fiber layer and ganglion cell layer in patients with thyroid-associated orbitopathy, including in the inactive phase and prior to the clinical manifestation of dysthyroid optic neuropathy. It may be a helpful adjunct in monitoring disease progression.